Backwater effect at Sungai Maong Kiri. - Basil, Anak Benjamin (Universiti Malaysia Sarawak, UNIMAS, 2009)
Sungai Maong Kiri is one of the rivers in Sungai Sarawak River Basin that may face flood tendency because Sungai Maong Kiri is under tidal influence. Backwater analysis is carried out to investigate whether existing channel of Sungai Maong Kiri is still able to accommodate the volume of water comprises the discharge from upstream and high tide from downstream. Backwater effect will cause overflow at Sungai Maong Kiri existing channel. Hydrologic analysis by using Rational Formula has been carried out to achieve average peak discharge. Different Average Recurrence Interval (ARI) has been used as the upstream boundary condition during the steady flow analysis. Highest Astronomical Tide (HAT) 6.4m has been chosen as a downstream boundary condition. Highest Astronomical Tide data was collected from Sarawak Marine Department. Backwater analysis is carried out by using HEC-RAS 4.0 on steady flow analysis. From the result, the channel is still capable to accommodate the water from CH 0 to CH 20000 but water overflow from CH 25000 to CH 30780. To prevent overflow at existing channel and satisfy the standard freeboard size for open channel, a 0.4m and 0.6m height leeve has been proposed to build at both side of the channel along CH 0 to CH 30780.